OVEMPs and cVEMPs in patients with 'clinically certain' Menière's disease. (2nd October 2016) - Johnson, Sarah-Anne; O'Beirne, Greg A.; Lin, Emily; Gourley, John; Hornibrook, Jeremy
Abstract: Objective: To measure ocular vestibular-evoked myogenic potentials (oVEMPs) and cervical vestibular-evoked myogenic potentials (cVEMPS) in Menière's disease patients with confirmed cochlear hydrops and in the normal ears of volunteers. Methods: oVEMPs and cVEMPs were measured in 18 patients with a symptomatic diagnosis of Menière's disease and tone burst electrocochleographic confirmation of hydrops, and in the ears of 22 volunteers. Results: Threshold measures: For cVEMP: no significant differences between Menière's ears and controls; for oVEMP: significantly elevated thresholds in affected ears of Menière's ears compared with their unaffected ears, but not with controls. Latency measures: cVEMP N1 peaks were significantly prolonged compared with the left and right ears of controls, but not with the non-affected ear. Amplitude measures: cVEMP P1N1 and N1P2 measures were significantly reduced compared with the right ear of controls, but not with the non-affected ear; For oVEMP, N2P2 amplitudes were significantly reduced compared with both ears of controls but not with the non-affected ear. Conclusion: Abnormalities of oVEMPs and cVEMPs were found in 18 Menière's disease patients who had an independent confirmation of cochlear hydrops. The overlap of the results from Menière's patients compared with normal controls limits the use of VEMP abnormalities as a sole reliable diagnostic test for Menière's disease.